Inhibition of PHB1/PHB2 suppresses atherosclerotic plaque formation by interrupting PI3K/AKT/mTOR signaling - Mei Li; Xiaoyan Hu; Xinxin Hu; Fuhua Gao; Ying Cui; Xiaoqing Wei; Yuanhua Qin; Xiaohua An; Ying Zhao; Ying Gao (PLoS ONE, 2025)
Prohibitin 1 (PHB1) and prohibitin 2 (PHB2) are highly conserved proteins belonging to the stomatin-prohibitin flotillin-HflC/K (SPFH) protein superfamily. They are ubiquitously expressed and implicated in the regulation of cell proliferation, migration, and survival. However, the expression and biological functions of PHB1/PHB2 in atherosclerosis (AS) remain unclear. In the present study, an enzyme-linked immunosorbent assay was used to detect PHB1/PHB2 expression in the serum of patients with hyperlipidemia. The potential effect and mechanism of PHB1/PHB2 in apolipoprotein E-deficient (ApoE−/−) mice were also investigated. shRNA-PHB1 and shRNA-PHB2 lentiviruses were engineered and tail vein-injected into ApoE−/− mice fed a high-fat diet. IL-8, a proatherogenic cytokine, was used as an inducer in vitro. The effects of a PHB1/PHB2 knockdown on vascular smooth muscle cell (VSMC) proliferation, migration, and autophagy and endothelial cell (EC) adhesion were evaluated using methyl thiazolyl tetrazolium (MTT), Transwell migration, Boyden chamber, and monocyte adhesion assays, as well as transmission electron microscopy. Compared with the healthy subjects, PHB1/PHB2 expression was elevated in the serum of patients with hyperlipidemia. Animal experiments showed that downregulation of PHBs reduced the area of atherosclerotic lesions, and the expression of cyclinD1, MMP9, and LC3. In addition, in vitro experiments showed that downregulating PHB1/PHB2 expression under inflammatory stimulation reduced the adhesion, proliferation, migration, and autophagy of ECs and VSMCs by inhibiting the PI3K/Akt/mTOR pathway activation. Collectively, our findings showed that PHBs are activly associated with AS progression.